Eco-engineered vertical seawall panels with augmented habitat complexity can create a novel and biodiverse ecosystem in a coastal megacity - Thea E. Bradford; Juan Carlos Astudillo; Charlene Lai; Rainbow W.S. Leung; Jay J. Minuti; Rebecca L. Morris; Stephen J. Hawkins; Janet Kit Yan Chan; Cheryl K.C. Chu; Kenneth Mei Yee Leung (Marine Environmental Research, 2026)

Micro‐Refuges or Ecological Traps: Context‐Dependent Effects of Rock Pools on Intertidal Biodiversity Across Latitudes - Louise B. Firth; Andrea Desiderato; Antony M. Knights; J. David Aguirre; Juan C. Astudillo; Juan C. Azofeifa‐Solano; David T. Bilton; Su Yin Chee; Hartvig C. Christie; Ronaldo A. Christofoletti; Amelia Curd; Katherine A. Dafforn; et al. (Global Ecology and Biogeography, 2026)
Aim We investigated how local‐scale environmental heterogeneity influences biodiversity patterns across broad biogeographic gradients, using intertidal microhabitats as a model system within one of the most environmentally stressful ecosystems on Earth. Location Intertidal habitats at 26 locations (two rocky shore sites per location) across six continents, spanning 98° of latitude (38°S to 60°N). Time Period 2019–2022. Major Taxa Studied Algae, sessile and mobile invertebrates. Methods We compared biodiversity and thermal environments across contrasting microhabitats (rock pools and adjacent emergent rock) along a latitudinal gradient, sampling during environmentally ‘milder’ and ‘harsher’ periods. Biodiversity was quantified using multiple richness metrics (mean, total, unique taxa) and functional diversity. Results Microhabitat differences strongly influenced biodiversity patterns across latitude. Rock pools consistently supported higher taxonomic and functional diversity than emergent rock, irrespective of sampling period, reflecting their ability to buffer thermal extremes, particularly under harsher conditions. Mean species richness exhibited a non‐linear, s‐shaped latitudinal pattern, with lowest values near the equator and higher richness at mid‐latitudes, diverging from classical Latitudinal Diversity Gradient expectations. Biodiversity differences between microhabitats were greatest in temperate regions and diminished at low latitudes, where extreme conditions constrained diversity across habitats. Main Conclusions Local environmental heterogeneity can substantially modify, and in some cases obscure large‐scale biodiversity patterns. By mediating exposure to environmental stress, intertidal microhabitats provide insight into how fine‐scale variability interacts with latitudinal stress gradients to shape biodiversity distributions. Incorporating microhabitat variability into biogeographic frameworks is important for understanding global biodiversity patterns and predicting ecological responses to climate change.

A short review of immobilized nanostructured systems for arsenic removal in water purification - C.G. Morales-Amaya; P.D. Astudillo-Sánchez; L. Reynoso-Cuevas; R. Herrera-Mendoza; S.A. Lozano-Morales (Environmental Research, 2025)

Greening of grey and murky harbours: enhancing biodiversity and ecosystem functioning on artificial shorelines - Thea E. Bradford; Juan Carlos Astudillo; Charlene Lai; Rainbow W.S. Leung; Jay J. Minuti; Stephen Hawkins; Rebecca L. Morris; Janet K.Y. Chan; Kenneth Mei Yee Leung (Marine Pollution Bulletin, 2025)

Turning riprap into reefs: Integrating oyster shells into shoreline armouring - Thea E. Bradford; Chi C. Lo; Juan Carlos Astudillo; Rainbow W.S. Leung; Charlene Lai; Jay J. Minuti; Carmen K.M. Wong; Stephen J. Hawkins; Rebecca L. Morris; Kenneth Mei Yee Leung (Marine Pollution Bulletin, 2025)

Mexico ants: incidence and abundance along the Nearctic–Neotropical interface - Wesley Dáttilo; Miguel Vásquez‐Bolaños; Diana A. Ahuatzin; Reuber Antoniazzi; Edgar Chávez‐González; Erick Corro; Pedro Luna; Roger Guevara; Fabricio Villalobos; Ricardo Madrigal‐Chavero; Jéssica C. de Faria Falcão; Adrián Bonilla‐Ramírez; et al. (Ecology, 2020)
Mexico is one of the most biodiverse countries in the world, with an important proportion of endemism mainly because of the convergence of the Nearctic and Neotropical biogeographic regions, which generate great diversity and species turnover at different spatial scales. However, most of our knowledge of the Mexican ant biota is limited to a few well‐studied taxa, and we lack a comprehensive synthesis of ant biodiversity information. For instance, most of the knowledge available in the literature on Mexican ant fauna refers only to species lists by states, or is focused on only a few regions of the country, which prevents the study of several basic and applied aspects of ants, from diversity and distribution to conservation. Our aims in this data paper are therefore (1) to compile all the information available regarding ants across the Mexican territory, and (2) to identify major patterns in the gathered data set and geographic gaps in order to direct future sampling efforts. All records were obtained from raw data, including both unpublished and published information. After exhaustive filtering and updating information and synonyms, we compiled a total of 21,731 records for 887 ant species distributed throughout Mexico from 1894 to 2018. These records were concentrated mainly in the states of Chiapas ( n = 6,902, 32.76%) and Veracruz de Ignacio de la Llave ( n = 4,329, 19.92%), which together comprise half the records. The subfamily with the highest number of records was Myrmicinae ( n = 10,458 records, 48.12%), followed by Formicinae ( n = 3,284, 15.11%) and Ponerinae ( n = 1,914, 8.8%). Most ant records were collected in the Neotropical region of the country ( n = 12,646, 58.19%), followed by the Mexican transition zone ( n = 5,237, 24.09%) and the Nearctic region ( n = 3,848, 17.72%). Native species comprised 95.46% of the records ( n = 20,745). To the best of our knowledge, this is the most complete data set available to date in the literature for the country. We hope that this compilation will encourage researchers to explore different aspects of the population and community research of ants at different spatial scales, and to aid in the establishment of conservation policies and actions. There are no copyright restrictions. Please cite this data paper when using its data for publications or teaching events.

Antimicrobial Butyrolactone I Derivatives from the Ecuadorian Soil Fungus Aspergillus terreus Thorn. var terreus - M. E. Cazar; G. Schmeda-Hirschmann; L. Astudillo (World Journal of Microbiology and Biotechnology, 2005)

Secondary metabolites from endophytic fungi isolated from the Chilean gymnosperm Prumnopitys andina (Lleuque) - G. Schmeda-Hirschmann; E. Hormazabal; L. Astudillo; J. Rodriguez; C. Theoduloz (World Journal of Microbiology and Biotechnology, 2005)

Biotransformation of solidagenone by Alternaria alternata, Aspergillus niger and Curvularia lunata cultures - G. Schmeda-Hirschmann; L. Astudillo; J.A. Palenzuela (World Journal of Microbiology and Biotechnology, 2004)

Fumonisins and Fungal Species in Corn from Sonora, Mexico - M. O. Cortez-Rocha; W. R. Ramrez-Astudillo; R. I. Snchez-Mariez; E. C. Rosas-Burgos; F. J. Wong-Corral; J. Borboa-Flores; L. G. Castilln-Campaa; M. Tequida-Meneses (Bulletin of Environmental Contamination and Toxicology, 2003)

Heavy Metals in Green Mussel ( Perna viridis ) and Oysters ( Crassostrea sp.) from Trinidad and Venezuela - L. Rojas de Astudillo; I. Chang Yen; J. Agard; I. Bekele; R. Hubbard (Archives of Environmental Contamination and Toxicology, 2002)

Acetophenone derivatives from Chilean isolate of Trichoderma pseudokoningii Rifai - L. Astudillo; G. Schmeda-Hirschmann; R. Soto; C. Sandoval; C. Afonso; M.J. Gonzalez; A. Kijjoa (World Journal of Microbiology and Biotechnology, 2000)